2015
DOI: 10.1016/j.jand.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Folate, Vitamin B-6, and Vitamin B-12 Intake and Mild Cognitive Impairment and Probable Dementia in the Women’s Health Initiative Memory Study

Abstract: Background Whether higher B vitamin (B6, B12, and folate) intake is protective against cognitive decline in later life remains uncertain. Several prospective, observational studies find higher B vitamin intake to be associated with lower risk of dementia; other studies, including most trials of B vitamin supplementation, observe no effect on cognition. We examine this question in a large population of older women carefully monitored for development of mild cognitive impairment (MCI) and probable dementia. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 58 publications
5
46
1
1
Order By: Relevance
“…Many clinical trials investigating HCY reduction as a potential modifiable risk factor employed vitamin B6, B12, and folic acid (B9) to reduce HCY although the clinical benefit is still under debate [81-84]. The inconsistent results of clinical trials may partly be due to unexplained genetic factors influencing HCY.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials investigating HCY reduction as a potential modifiable risk factor employed vitamin B6, B12, and folic acid (B9) to reduce HCY although the clinical benefit is still under debate [81-84]. The inconsistent results of clinical trials may partly be due to unexplained genetic factors influencing HCY.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that food fortification could reduce the long term risk of cognitive impairment. 17 As has been stated previously, the phenomenon that Smith and colleagues report is probably the result of people who have untreated vitamin B 12 deficiency taking multivitamin supplements. 18 19 Such people would absorb the folic acid, resulting in high folate concentrations, but would not absorb the vitamin B 12 .…”
mentioning
confidence: 83%
“…Similarly, in the HAPIEE (health, alcohol and psychosocial factors in Eastern Europe) study comprising 4,166 participants, folate and vitamin B12 were positively associated with performance (verbal fluency, immediate recall) [41]. In addition, in 7,030 postmenopausal women without memory cognitive impairment or probable dementia, monitored for over 5 years, those with folate intake below the recommended daily allowance were associated with increased risk of mild cognitive impairment and probable dementia [42]. Conversely, a 2 year folic acid and vitamin B12 supplementation study in 2,919 individuals over 65 years of age with high homocysteine levels, showed no beneficial effects on performance on 4 cognitive domains, although a small improvement in global cognition was noted [43].…”
Section: 4mentioning
confidence: 95%